2020
DOI: 10.1021/acsaem.9b02200
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Silicon Fragmentation in Lithium Ion Battery Anodes Using Electronic Doping Strategies

Abstract: Although Si anodes have the potential to achieve gravimetric capacities >3000 mA g −1 for Li ion batteries, their utility has been limited by their large volumetric expansion on lithiation and electrode fragmentation. We show that n-type doping reduces the lithiation potential of (100) Si and conclude that the Li ion insertion energy into crystalline Si increases with ntype dopant density. This allows tuning of the n-type dopant density in Si electrodes to reduce surface fragmentation and increase electrode cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 64 publications
1
36
0
Order By: Relevance
“…On the contrary, the capacity of the LIB with an n-SiNW electrode demonstrated capacity retention of 76.7% at 0.2 mA cm −2 , and restored 97.1% of its capacity when the discharge rate was reduced back to 0.02 mA cm −2 . In this case, the vertical arrangement of the nanowires provided a facile and fast Li ion diffusion pathway, resulting in the measured improved capacity retention at high current rates [15,43]. The good rate performance of LIBs with n-SiNW electrodes is also ascribed to the fast infiltration and circulation of the electrolyte in the nanowire array electrode, facilitating rapid ion transport during the electrochemical reactions [8].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…On the contrary, the capacity of the LIB with an n-SiNW electrode demonstrated capacity retention of 76.7% at 0.2 mA cm −2 , and restored 97.1% of its capacity when the discharge rate was reduced back to 0.02 mA cm −2 . In this case, the vertical arrangement of the nanowires provided a facile and fast Li ion diffusion pathway, resulting in the measured improved capacity retention at high current rates [15,43]. The good rate performance of LIBs with n-SiNW electrodes is also ascribed to the fast infiltration and circulation of the electrolyte in the nanowire array electrode, facilitating rapid ion transport during the electrochemical reactions [8].…”
Section: Resultsmentioning
confidence: 96%
“…The diffraction peak at 2θ = 69.13 • for the plain/blank Si wafer and the n-SiNW corresponds to the <400> crystal orientation as the first reflection from <100>-Si [42]. An n-type Si with <100> orientation enables faster diffusion of Li ions, which is beneficial for reducing the volume expansion of Si anodes [43].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have been conducted to solve the abovementioned issues. These include reducing the size of the Si particles to prevent generation of stress, , doping Si with impurities, such as boron and phosphorous, to suppress the Si-to-Li 15 Si 4 phase transition, and/or increasing its electrical conductivity, , and preparing lithium silicides to decrease the relative volume change in Si during charge–discharge cycles . Other approaches involve coating Si with conductive materials to lower the electrical resistivity , or synthesizing Si-based alloys to enhance the stability of the electrode structure during cycling. Moreover, film-forming additives or ionic liquid electrolytes have been utilized for the construction of an optimal solid–electrolyte interphase. Lastly, composites have been prepared to improve the mechanical properties …”
Section: Introductionmentioning
confidence: 99%
“…Although the optimization of the conductive additive, , binder, , powder size, , and electrode structure , is effective in improving the electrical conductivity of the entire electrode and accommodating volume expansion and contraction for achieving a long-cycle life, it is difficult to enhance the Li + diffusion coefficient and the electrical conductivity of Si as a bare material. As a typical method of improving its properties, doping of impurity into Si has been considered: O’Dwyer et al reported that a higher current response was observed during cyclic voltammetry using n-type Si with the B dopant compared with that of p-type Si with the As dopant (doping density: 1.2–7.4 × 10 19 atoms cm –3 and 240–1480 ppm) . Greeley and Gewirth et al studied the energetics and kinetics of Li insertion into p-type and n-type crystalline Si using the B-doped and P-doped Si wafers with two crystallographic faces of (100) and (111) .…”
Section: Introductionmentioning
confidence: 99%